Paradiplomacy Capacity of the Kepulauan Riau Provincial Government in Optimizing Regional Economic Connectivity - Rizqi Apriani Putri; Yudithia Yudithia; Anastasia Wiwik Swastiwi; Annissa Valentina (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study examines the paradiplomacy capacity of the Kepulauan Riau Provincial Government in optimizing regional economic connectivity. In the context of globalization and regional integration, paradiplomacy has become a crucial instrument for subnational governments to expand cross-border cooperation and enhance economic competitiveness. The main issue addressed concerns the extent to which the institutional, regulatory, and resource capacities of the Riau Islands Government are able to support subregional economic diplomacy within the framework of the Indonesia–Malaysia–Thailand Growth Triangle (IMT-GT). This research employs a qualitative method with a descriptive approach, utilizing policy document analysis, in-depth interviews, and secondary data from relevant institutions. The findings indicate that paradiplomacy practices in the Riau Islands have significantly contributed to increasing foreign investment, exports, and strengthening cross-border logistics networks. Furthermore, collaboration among local governments and the private sector has fostered the development of halal tourism, the creative economy, and the digitalization of regional connectivity. However, challenges remain, particularly in legal harmonization and inter-agency coordination. This study concludes that enhancing institutional capacity and human resources is essential for the success of subnational paradiplomacy in strengthening regional economic connectivity and achieving inclusive and sustainable growth.